Application of the TGT Type Cooperative Learning Model to Improve Student Learning Outcomes in Social Studies Subject Class V SD Negeri 14 Loghia - La Ode Butu (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
The purpose of this study was to improve learning outcomes through the TGT learning model in social studies subjects for fifth grade students of SD Negeri 14 Loghia. The implementation procedure is carried out with a cycle assessment process consisting of 4 (four) stages, namely: planning, implementing actions, observing and evaluating and reflecting. The results showed that the application of the TGT type cooperative learning model for social studies learning outcomes for fifth graders at SD Negeri 14 Loghia could be improved. This can be seen in the results of research on performance indicators on actions in terms of the learning implementation process and in terms of learning outcomes achieved such as. In terms of student learning outcomes, in the first cycle students obtained a score of 65 or completed as many as 11 people (55%) and who had not completed as many as 9 people (45%) in the second cycle who completed as many as 19 people (95%) and who had not completed 1 person (5%). This shows that the number and percentage of students who have completed learning in social studies subjects increased in cycle II and the student learning process at SD Negeri 14 Loghia has been completed. The increase in student learning outcomes cannot be separated from the increase in teacher teaching activities. The implementation of the learning scenario carried out by the teacher when teaching in the first cycle was 65.9% and in the second cycle it was 86.35% and has reached the implementation standard that has been set, which is 80%. As for student learning activities also experienced similar results, student activity in the first cycle was 53.57% and increased in the second cycle to 85.71% and was said to be complete based on the predetermined KKM.